Review: Ming-sum Tsui (2005). Social Work Supervision. Context and Concepts - Laila Niklasson (Forum: Qualitative Social Research, 2006)
Supervision in professional organizations is a task that was focused on during the late 20th century. The view of a professional as having a certain amount of everlasting knowledge and skills has changed to a view where the profession is constructed in everyday practice in a cultural context. With this later view supervision is an important part in the construction of the profession. Supervision is especially worthwhile problematizing when the profession includes day-to-day meetings with, for example, clients. In Social Work Supervision the history of supervision is described and theoretical models constituting supervision are presented. Different modes of the interaction between the supervisee and the supervisor are problematized. The context of the supervision can affect whether the focus is on the administrative, educational or the supportive function. Whatever the function the supervision includes stages, strategies and skills for the supervisee as well as for the supervisor. In a strictly structured and informative argument TSUI argues the importance of highlighting both the practice and theory of supervision, and addresses several actors. As the author mentions, supervision is interrelational and contextual and, therefore, my suggestion is that the discussion addresses questions that are relevant for those already in a profession (social worker, social work teachers, managers and decision makers in organizations). For those who are already professionals, in any respect, TSUI's arguments provide fruit for discussion in an organizational setting. The holistic, cultural perspective for which TSUI is arguing also suggests a research perspective. To this I would add that supervision can be discussed in the context of research into professionalism and lifelong learning. URN: urn:nbn:de:0114-fqs0603239